Benzopyrene Induces Oxidative Stress and Increases Expression and Activities of Antioxidant Enzymes, and cyp450 and Gst Metabolizing Enzymes in Ulva Lactuca (Chlorophyta) - Moenne-Munoz, A; Gonzalez-Figueroa, A; Espinoza-Majmud, D (Springer Science and Business Media Deutschland GmbH, 2020)
Main conclusion: Benzopyrene is rapidly incorporated and metabolized, and induces oxidative stress and activation of antioxidant enzymes, and CYP450 and GST metabolizing enzymes in Ulva lactuca. Abstract: To analyze absorption and metabolism of benzo[a]pyrene (BaP) in Ulva lactuca, the alga was cultivated with 5 µM of BaP for 72 h. In the culture medium, BaP level rapidly decreased reaching a minimal level at 12 h and, in the alga, BaP level increased until 6 h, remained stable until 24 h, and decreased until 72 h indicating that BaP is being metabolized in U. lactuca. In addition, BaP induced an initial increase in hydrogen peroxide decreasing until 24 h, superoxide anions level that remained high until 72 h, and lipoperoxides that initially increased and decreased until 72 h, showing that BaP induced oxidative stress. Activities of antioxidant enzymes superoxide dismutase (SOD), catalase (CAT), ascorbate peroxidase (AP), glutathione reductase (GR) and glutathione peroxidase (GP) were increased, whereas dehydroascorbate reductase (DHAR) activity was unchanged. The level of transcripts encoding these antioxidant enzymes was increased, but transcripts encoding DHAR remained unchanged. Interestingly, the activity of glutathione-S-transferase (GST) was also increased, and inhibitors of cytochrome P450 (CYP450) and GST activities enhanced the level of BaP in algal tissue, suggesting that these enzymes participate in BaP metabolism. © 2020, Springer-Verlag GmbH Germany, part of Springer Nature.